Management of Pain in Chronic Pancreatitis with Home Elemental Diet Ingestion - Ito, Tetsuhide; Igarashi, Hisato; Niina, Yusuke; Hijioka, Masayuki; Matsuo, Susumu; Shimokawa, Yuzo; Yonekura, Michitaka; Nakamura, Kazuhiko; Takayanagi, Ryoichi (JOP. Journal of the Pancreas, 2010)
No abstract available. Image: Abdominal enhanced CT in a patient with calcified chronic pancreatitis.